Reframing neurodiversity in engineering education - Chrysochoou, Maria; Zaghi, Arash E.; Syharat, Connie Mosher (Frontiers in Education, 2022)
A growing body of literature suggests that neurodiverse learners may possess assets that are highly desirable within engineering disciplines. Even so, despite the potential of neurodiverse individuals to contribute to innovation in science and engineering, neurodiverse students, such as those with ADHD, autism, or dyslexia, remain highly underrepresented in engineering majors. We argue that the predominant perception of neurodiversity as disability limits the participation of neurodiverse students in engineering education, ultimately impacting the diversity and creativity of the engineering workforce. In this paper, we review the emerging literature on neurodiversity that takes a social ecology approach and moves away from deficit-based models. We then describe the potential benefits and challenges of neurodiversity in the context of engineering education. We conclude with a discussion of how a strengths-based perspective of neurodiversity may be integrated within engineering education in particular, as well as in higher education overall, as we present our vision for a transformative education system that moves beyond mere accommodation of learning differences and empowers all students to leverage their unique strengths. In presenting a strengths-based approach to neurodiversity , we aim to contribute to a paradigm shift that transforms how university faculty and staff understand and perceive neurodiversity, improves the educational experiences of neurodiverse students in higher education and enhances the creativity of the engineering workforce.